Suture tape anchors for enhancing healing in rotator cuff tears: a retrospective cohort study - Shixin Nie; Hao Qin; Hao Tan; Pei Zhao; Wenlong Yan; Aiguo Zhou; Jian Zhang; Chengjie Lian; Hua Zhang (BMC Musculoskeletal Disorders)
Abstract Background Rotator cuff injuries are common, particularly among older adults, and are often treated with arthroscopic repair. However, retear rates remain high. This study compares clinical and structural outcomes between arthroscopic double-row suture bridge repairs using either suture tape anchors (STAs) with knotless medial fixation, or traditional knotted suture anchors (TSAs) with knotted medial fixation. Methods This retrospective cohort study compared arthroscopic double-row suture bridge repairs performed from January 2021 to July 2023 using either knotless STAs or knotted TSAs. Eligible patients had medium (1–3 cm), large (3–5 cm), or massive (> 5 cm) full-thickness rotator cuff tears (DeOrio-Cofield classification) with no greater than Goutallier grade 3 fatty infiltration. Clinical outcomes were measured using VAS, Constant, UCLA, and ASES scores, both preoperatively and at 1-year postoperative follow-up. Muscle strength was assessed using manual muscle testing (0–5 scale) with the arm positioned at 30° scapular elevation. Structural outcomes were evaluated via MRI, where two trained surgeons assessed tendon thickness using the Sugaya classification and identified retears according to the Cho classification. Statistical analysis was conducted using SPSS. Results The study included 86 consecutive patients undergoing arthroscopic rotator cuff repair, with 36 patients in the STA group (median follow-up 15.0 months, range 12–19 months) and 50 patients in the traditional suture anchor (TSA) group (median follow-up 16.5 months, range 12–20 months). Both groups showed significant improvements in functional scores (VAS, Constant, UCLA, ASES) postoperatively (P < 0.05), with no significant differences between the two groups (P > 0.05). The STAs group had significantly lower tendon thinning and higher tendon thickness and supraspinatus muscle strength compared to the TSAs group (P < 0.05). The retear rate was similar between the two groups (12.0% for TSAs and 11.1% for STAs, P > 0.05). Conclusions At 1 year, both STAs and TSAs showed favorable clinical outcomes, but STAs were more effective in preserving tendon thickness and improving muscle strength. Although retear rates were similar, STAs may offer advantages in tendon healing and functional recovery. Clinical trial number Not applicable.